2015
DOI: 10.1016/j.sdentj.2015.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polyester fiber reinforcement on the mechanical properties of interim fixed partial dentures

Abstract: Within the limitations of this study, polyester fiber reinforcements improved the mechanical properties of heat-polymerized PMMA, cold-polymerized PMMA, and bis-acrylic provisional FPD materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Polyester, commonly used for reinforcement coatings, has been incorporated into silicones [ 28 , 29 ] because of its great toughness and flexibility, as well as high weather durability, strength and heat resistance properties [ 30 , 31 ]. Haider et al [ 28 ] used polyester powder at 1%, 3% and 5% concentrations, with significant tensile and tear resistance changes observed at 1%.…”
Section: Discussionmentioning
confidence: 99%
“…Polyester, commonly used for reinforcement coatings, has been incorporated into silicones [ 28 , 29 ] because of its great toughness and flexibility, as well as high weather durability, strength and heat resistance properties [ 30 , 31 ]. Haider et al [ 28 ] used polyester powder at 1%, 3% and 5% concentrations, with significant tensile and tear resistance changes observed at 1%.…”
Section: Discussionmentioning
confidence: 99%
“…It had opened doors for the use in an extended period specifically in necessary prognosis for example in a two-step surgical approach in dental implants which requires more than six months of temporary restoration and in acquiring the exact diagnostic information prior to a definitive restoration. 5,6,7,8,9 In 2015, Hameed and Rahman stated that the incorporation of inorganic nanoparticles into PMMA alters the properties of the product depending on the type, sizes and shapes, concentration and interaction within the polymer matrix itself. Attempts were made to increase the mechanical properties, biological properties and most importantly the optical properties through the incorporation by adding filler particles with different elements such as zirconia, silica, alumina, glass fiber, tin and copper to PMMA.…”
Section: Introductionmentioning
confidence: 99%
“…As 3D printing continues to become a commonplace addition to chair side dental clinics, the evolution of these materials, in particular reinforced PMMA, resin incorporating zirconia and glass reinforced polymers offer increased speed and improved aesthetics that will likely replace subtractive manufacturing milling machines for most procedures. [44,45] Literature Search Details: The literature chosen was selected with eligibility criteria between the dates 1970 to the date the search was made on the 05/03/2019. The search was limited to;…”
Section: Discussionmentioning
confidence: 99%
“…[39] Therefore, if 3D printing resin can incorporate graphene or polyethylene fibres into the polymer matrix, this should result in a stronger restoration. [44,45] Hamza, Johnston and Schricker [43] assessed this reinforcement effect following the addition of 1% of the polyhedral oligomeric silsesquioxane (POSS). The results indicated that "the reinforcement effect of POSS on flexural strength depended on the brand", suggesting that particular chemical composition of the provisional materials determines the ability of POSS to improve their mechanical properties, which may mean that some 3d printer resin brands may perform better than others even if based on similar material technology.…”
Section: Future Developments With Graphene and Fibreglass Reinforcementmentioning
confidence: 99%